Couplings in cell differentiation kinetics mitigate air temperature influence on conifer wood anatomy. (19th November 2018) - Cuny, Henri E.; Fonti, Patrick; Rathgeber, Cyrille B.K.; von Arx, Georg; Peters, Richard L.; Frank, David C.
Abstract: Conifer trees possess a typical anatomical tree‐ring structure characterized by a transition from large and thin‐walled earlywood tracheids to narrow and thick‐walled latewood tracheids. However, little is known on how this characteristic structure is maintained across contrasting environmental conditions, due to its crucial role to ensure sap ascent and mechanical support. In this study, we monitored weekly wood cell formation for up to 7 years in two temperate conifer species (i.e., Picea abies (L.) Karst and Larix decidua Mill.) across an 8°C thermal gradient from 800 to 2, 200 m a.s.l. in central Europe to investigate the impact of air temperature on rate and duration of wood cell formation. Results indicated that towards colder sites, forming tracheids compensate a decreased rate of differentiation (cell enlarging and wall thickening) by an extended duration, except for the last cells of the latewood in the wall‐thickening phase. This compensation allows conifer trees to mitigate the influence of air temperature on the final tree‐ring structure, with important implications for the functioning and resilience of the xylem to varying environmental conditions. The disappearing compensation in the thickening latewood cells might also explain the higher climatic sensitivity usually found in maximum latewood density. Abstract : The structure of conifer wood cells depends on the speed and duration of processes shaping their formation. In this study, we show for the first time that cells growing at colder sites increase their duration of their processes to compensate for a speed reduction. This compensation allows conifers to mitigate the effect of air temperature to maintain a more similar tree‐ring structure despite contrasting conditions.